2008
DOI: 10.1200/jco.2007.15.7867
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Risk of Cancer in Postmenopausal Korean Women

Abstract: Although variations exist between the individual cancer sites, obesity was associated with an overall increased risk of cancer in postmenopausal Korean women. To reduce the risk of cancer, active strategies to prevent obesity should be implemented in postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
76
1
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(82 citation statements)
references
References 39 publications
3
76
1
2
Order By: Relevance
“…A significantly higher number of patients were postmenopausal (61.96%) as compared to controls (30.44%). In previous reports, an increased risk of breast and endometrial cancers has been reported in postmenopausal obese women in the Western (Reeves et al, 2007), Korean (Song et al, 2008), as well as Asian population (Kuriyama et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…A significantly higher number of patients were postmenopausal (61.96%) as compared to controls (30.44%). In previous reports, an increased risk of breast and endometrial cancers has been reported in postmenopausal obese women in the Western (Reeves et al, 2007), Korean (Song et al, 2008), as well as Asian population (Kuriyama et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Now, 2 cohort studies have been reported from Asia. Oh et al 8 reported that a BMI of 25.0-29.9 kg/m 2 was associated with a 54% higher NHL risk than a BMI of 18.5-22.9 kg/m 2 with marginal significance among Korean men, whereas Song et al 11 reported no association between BMI and ML risk among postmenopausal Korean women.…”
mentioning
confidence: 93%
“…[1][2][3][4][5][6][7][8][9][10][11] Moreover, most of these studies were conducted in non-Asian populations. Recently, the International Lymphoma Epidemiology Consortium (InterLymph) reported a large pooled analysis of 18 case-control studies conducted at various centers, including ours, to evaluate the impact of recent obesity on NHL risk, with the results suggesting no significant association between NHL and obesity.…”
mentioning
confidence: 99%
“…After full-text review of the remaining 31 studies, two studies were excluded because one study did not report RR with the corresponding 95% CI and the other study did not provide sufficient data to calculate them. Thus, 14 (7,(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47) cohort studies and 15 (19,(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61) case-control studies were included in this meta-analysis.…”
Section: Literature Searchmentioning
confidence: 99%